Caregivers' perceptions of the health of their overweight children: A qualitative study in Costa Rica - Núñez Rivas, Hilda Patricia (2025)
Introduction. Childhood obesity represents an increasingly complex challenge for global public health. In Costa Rica, approximately 30% of the school-age population is overweight, demanding a comprehensive and multidimensional approach. Objective. To explore the perceptions of caregivers of overweight schoolchildren from eleven elementary schools in San Pedro de Montes de Oca, Costa Rica regarding their children's health outcomes and the barriers they face in accessing the healthcare system. Methodology. A qualitative, exploratory, and phenomenological approach was adopted. Semi-structured telephone interviews were conducted with caregivers selected through convenience sampling, that is, those who were available and willing to participate at the time of the study. A thematic analysis was applied. Results. Emotional, cognitive, and structural dimensions emerged as factors influencing caregivers’ responses. Caregivers expressed surprise and concern regarding the clinical results, revealing a gap between visual perception of overweight and understanding of metabolic risks. Nonetheless, they valued the information received as a driver for change and reported taking immediate actions such as modifying diet and increasing physical activity. However, their efforts were constrained by inaccessible clinical language, inflexible work schedules, lack of clarity regarding procedures, and limited availability of specialists. Additionally, caregiving burdens and single parenthood further restricted their ability to follow up on medical recommendations. A transversal category reflected mixed views of the public healthcare system: caregivers acknowledged its importance but expressed frustration with delays and inefficiencies, which negatively affected their trust and adherence. Conclusions. Caregivers show a strong commitment to their children's health but face significant systemic barriers. Clearer communication, intersectoral strategies, and structural improvements focused on families are essential to ensure effective follow-up and continuity of care.